Nonlinear Coupler for Optical Fiber Mach-Zehnder Interferometer - Quy, Ho Quang; Sau, Vu Ngoc; Tam, Nguyen Thi Thanh; Hoa, Nguyen Van (Communications in Physics, 2012)
In this article the equations for two waves propagating in two fibers of nonlinear Kerr coupler for optical Mach-Zehnder interferometer are derived. Based on the resolution of those equations, the expressions describing relation between coherent length, input intensity of the wave, nonlinear coefficient of refractive index for 3dB Kerr coupler are introduced and discussed.